University Students' Attitudes Towards EFL: A Case From the South of Chile - Eric Gómez Burgos; Soledad Sandoval Molina (Universidad Nacional de Colombia, 2020)
Attitude towards English as a foreign language is a new field of study in tertiary education in Latin-American countries, especially in Chile. However, its importance in the process of learning a language has been reported upon around the world. The aim of the current study was to identify the attitudes towards English as a foreign language of 131 university students from different educational institutions in Chile; the students' programs included English courses as part of their study plan. The three components of attitude were analyzed by means of the participants' replies to the statements of a questionnaire. Results gave evidence that university students hold a positive attitude towards English as a foreign language; nonetheless, the behavioral aspect of attitude obtained the lowest average of agreement among the respondents.